Produção e comercialização de alimentos orgânicos: considerações acerca da experiência de camponeses ligados ao CETAP de Erechim - RS - Peccini, Michel Diego (2014)
The capitalist modernization of agriculture promoted a series of transformations of rural area. Mechanization, chemical inputs and transgenic seeds started to compromise the sustainable rural development and alienate the peasants. In front of this context, the search looked for treat the theme “Production and commercialization of organic food: considerations about experiences of peasants linked to CETAP of Erechim – RS”. For it approached the problematic: How sustainable, environmentally, economically, socially, politically and culturally is the production and marketing of organic food developed by peasants linked to CETAP? This paper aims to analyze the production and marketing of organic food developed by 15 peasant families linked to CETAP in the perspective of sustainable rural development. To achieve this objective, more punctually, it was surched by the specific objectives: 1) Characterize which organic foods are produced and marketed by peasants linked to CETAP and if these foods assist in increasing diversification and ecological preservation in agricultural units; 2) To evaluate if the production and marketing of organic foods contribute to the reduction of the economic dependence of peasants linked to CETAP; 3) To verify if the production and marketing of organic foods help to improve the quality of life of peasants linked to CETAP; 4) To understand if the production and marketing of organic foods contribute to the cooperation and organization of peasants linked to CETAP; 5) To investigate if the production and marketing of organic food addresses the cultural aspects and traditional knowledge of peasants linked to CETAP. The hypothesis was that the production and marketing of organic food contribute to sustainable rural development and are fundamental to emancipation Human of peasants linked to CETAP. To effect the serach, the following methods were adopted: a bibliographic review and a case study with 15 families of peasants through semi-structured interviews with peasants who produce and commercialize organic foods linked to CETAP in the region of Alto Uruguai – RS and the region of Meio-Oeste – SC. Furthermore, visits were made with the peasants and CETAP technicians. Quantitative and qualitative methodological approaches were used for analysis and data interpretation. In this research, it has been noted that the production and marketing of organic food have been a strategy of peasants concerned with a sustainable environment, a viable economy, a just and equitable society, a participative politics, a plural culture, a solidariy ethics and economy. The Ecovida Network of Agroecology and the Center of Popular Alternative Technologies (CETAP) have played a fundamental role in monitoring and strengthening of peasants in their production and commercialization of organic foods. Finally, it was found that the production and marketing of organic food, on bases and on agro-ecological principles, are fundamental to sustainable rural development and the human emancipation of peasants and has helped to build a new historical context.